2013
DOI: 10.3171/2013.6.spine12927
|View full text |Cite
|
Sign up to set email alerts
|

Tumor control after surgery for spinal myxopapillary ependymomas: distinct outcomes in adults versus children

Abstract: Object Myxopapillary ependymomas (MPEs) are rare WHO Grade I tumors found in the conus medullaris, cauda equina, and filum terminale. Treatment generally consists of resection with or without adjuvant radiotherapy. Evidence-based guidelines for surgical management are lacking due to the rarity of this tumor. Methods An English-language PubMed search was performed using the key words “myxopapillary” and “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 37 publications
1
63
1
3
Order By: Relevance
“…The total recurrence rate was 15.5% in 232 patients who underwent complete resection, compared with 32.6% in 135 patients who underwent partial resection. 9 Though not exclusively MPEs, in 31 cases of spinal ependymomas Chang et al also found a correlation between extent of resection and PFS. 6 Neither of these studies, however, differentiated between gross-total removal with capsular violation (en bloc) and GTR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The total recurrence rate was 15.5% in 232 patients who underwent complete resection, compared with 32.6% in 135 patients who underwent partial resection. 9 Though not exclusively MPEs, in 31 cases of spinal ependymomas Chang et al also found a correlation between extent of resection and PFS. 6 Neither of these studies, however, differentiated between gross-total removal with capsular violation (en bloc) and GTR.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,15 In the large systematic analysis by Feldman et al, radiotherapy did not improve the overall tumor recurrence regardless of the extent of resection. 9 In our study, no patient with an en bloc resection underwent adjuvant radiotherapy. Of those with capsular violation (GTR or STR), we did find a trend of lower recurrence rates (16.7% vs 31.6%, p = 0.43) and longer PFS at 5 years (83.3% vs 49.9%, p = 0.16) in patients who received adjuvant radiotherapy.…”
Section: Fig 2 Influence Of Extent Of Resection On Pfs Kaplan-meiementioning
confidence: 99%
See 2 more Smart Citations
“…21 Myxopapillary ependymomas should be treated according to this policy as well, aiming for a GTR regardless of their size. 12,23 The strategy for small tumors is to attempt in toto removal, with resection of the filum. With large tumors filling out the spinal canal completely and/ or extending cranially beyond the conus, en bloc removals are impossible without significant neurological deficits and should not be attempted.…”
Section: Surgical Managementmentioning
confidence: 99%